The other guys [videorecording (DVD)] - McKay, Adam, 1968-; Wahlberg, Mark, 1971-; Jackson, Samuel L.; Ferrell, Will, 1967-; Jeter, Derek, 1974-; Johnson, Dwayne, 1972-; Mendes, Eva, 1974-; Keaton, Michael, 1951-; Coogan, Steve (Sony Pictures Home Entertainment, 2010)
When two mismatched NYPD detectives stumble into a seemingly dull case that no other detective wants to bother with, it turns out to be New York City's biggest crime. The two seize the opportunity to step up like the city's top cops, whom they idolize. But do these two guys have the right stuff?